2022
DOI: 10.1186/s13024-022-00589-x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-beta and tau pathologies act synergistically to induce novel disease stage-specific microglia subtypes

Abstract: Background Amongst risk alleles associated with late-onset Alzheimer’s disease (AD), those that converged on the regulation of microglia activity have emerged as central to disease progression. Yet, how canonical amyloid-β (Aβ) and tau pathologies regulate microglia subtypes during the progression of AD remains poorly understood. Methods We use single-cell RNA-sequencing to profile microglia subtypes from mice exhibiting both Aβ and tau pathologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 104 publications
4
25
1
Order By: Relevance
“…CITE-Seq did not reveal a subpopulation unique to the K18+P301L model, but we did observe a modest increase in the DAM population, consistent with other single-cell RNA sequencing studies in other tauopathy models, such as TE4 mice (P301S expressing human APOE4) and Tau4RΔK-AP mice (Chen et al, 2023; Kim et al, 2022). In line with the Tau4RΔK-AP mice study, the increase of the DAM subpopulation was only observed at late stages of hyperphosphorylated tau spreading (Kim et al, 2022). Furthermore, there was no one-on-one relationship between DAM emergence and hyperphosphorylated tau load.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CITE-Seq did not reveal a subpopulation unique to the K18+P301L model, but we did observe a modest increase in the DAM population, consistent with other single-cell RNA sequencing studies in other tauopathy models, such as TE4 mice (P301S expressing human APOE4) and Tau4RΔK-AP mice (Chen et al, 2023; Kim et al, 2022). In line with the Tau4RΔK-AP mice study, the increase of the DAM subpopulation was only observed at late stages of hyperphosphorylated tau spreading (Kim et al, 2022). Furthermore, there was no one-on-one relationship between DAM emergence and hyperphosphorylated tau load.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies suggest that microglial activation can accelerate tau aggregation and behavioural abnormalities in a hTau mouse model (Bhaskar et al, 2010; Chen et al, 2023; Gratuze et al, 2023; Sierksma et al, 2020; C. Wang et al, 2022), and that the accumulation of senescent microglia contributes to tau aggregation in a hTau.P301S (PS19) mouse model (Bussian et al, 2018). While there have been some studies investigating microglial subpopulations in models of tauopathy and in human brains (Chen et al, 2023; Gerrits et al, 2021; Kim et al, 2022), there is a lack of a comprehensive understanding of the influence of tau on microglia and the evolution of microglial heterogeneity during tau pathology progression. Furthermore, considering that microglia are long-lived cells, and that the most important risk factor for neurodegeneration is age, it can be expected that age-associated changes in microglia prime for pathology as well (Yoo & Kwon, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The association between microglia, astrocyte with AD pathologies has not been fully understood. Aβ and tau pathologies have been shown to exert distinct influences and induce disease stage-specific microglial subtypes (25, 35). Microglial activation measured by PET using tracer for translocator protein is found associated with AD amyloid and tau pathology (58).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix files generated from the Cellranger run were used for subsequent analysis as described previously (18, 23). Briefly, Seurat V3 (24) was used to perform downstream analysis, only including cells with more than 500 genes, and 1000 UMI, to process control and treated samples separately.…”
Section: Methodsmentioning
confidence: 99%